Comparative study of project management and critical success factors of greening new and existing buildings in Singapore. Issue 5 (4th November 2014) - K. Ahadzie, Divine; A. Ankrah, Nii; Pheng Low, Sui; Gao, Shang; Lin Tay, Wen
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – With pressing issues of climate change, greening buildings have emerged as a viable solution for meeting the increasing demand for buildings with minimal environmental impacts. Hence, the purpose of this paper is to establish the possibility of achieving this goal by investigating the drivers, challenges, and critical success factors (CSFs) involved in greening existing buildings. Since most of the relevant literature focuses on only acknowledging CSFs for new building projects in general, this study seeks to distinguish CSFs that are particularly related to the greening of existing buildings. Design/methodology/approach – Based on a review of past literature, 28 selected factors were identified and were categorised into five main groups, namely pre-project-related factors, project management-related factors, client-related factors, project team-related factors, and external factors. Because older buildings have more constraints than new buildings, a comparison of the CSFs for greening new and existing buildings was also made. Surveys and interviews were conducted to validate the CSFs identified. Findings – The top CSFs in each building category (new vs existing) were then further examined and analysed. These are "top management support", "effective planning and control", "building owner's involvement", "cost management", "responsiveness of building owners", "clear scope and priorities of stakeholders", and "legislation". Furthermore, there was a strong consensus on the rankings of most factors between new and existing buildings. Research limitations/implications – By understanding the factors that are crucial for managing and delivering successful green projects in the Singaporean context, these CSFs can be used to direct an organisation's efforts in identifying critical issues and tackling them to achieve high performance. Originality/value – An ambitious goal of greening 80 per cent of Singapore's building stocks has been set by the government in the Second Green Building Master Plan. To help achieve this goal, this study contributes to the knowledge of project management issues that would determine the success of managing new green building projects and retrofitting existing ones.